Low-carbon olefin hydration catalyst, preparation method thereof and method for producing low-carbon alcohol aqueous solution
By grafting the adsorption layer and the reaction layer on the resin white sphere matrix catalyst, the water olefin contact efficiency is improved by using specific group combinations, the existing low-carbon olefin hydration catalysts are solved, and efficient low-carbon alcohol production is achieved.
Patent Information
- Application Number
- CN202311218059.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-09-20
AI Technical Summary
The existing low-carbon olefin hydration catalysts have insufficient activity and structure, resulting in low olefin hydration conversion and low-carbon alcohol yield and selectivity.
A resin white sphere matrix is used as a catalyst matrix, and the adsorption layer and the inner surface grafting reaction layer are grafted on its outer surface, and the adsorption layer and the reaction layer contain specific groups combinations to improve the contact and reaction efficiency of water ene.
The contact between the hydrene and the catalyst surface is significantly improved, the hydration conversion rate is improved, the yield and selectivity of low-carbon alcohols are enhanced, and the catalyst activity is relatively stable.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-carbon olefin hydration, and in particular to a low-carbon olefin hydration catalyst and a preparation method thereof, and a method for producing a low-carbon alcohol aqueous solution. Background Art
[0002] Olefin hydration is one of the important organic reactions and can be used to prepare alcohols, such as sec-butyl alcohol, isopropyl alcohol, cyclohexanol, etc. Traditional olefin hydration generally adopts sulfuric acid indirect hydration method, which has serious equipment corrosion problems and waste acid treatment problems, and has gradually been replaced by catalytic direct hydration method. Catalytic direct hydration method generally uses solid acid catalyst to directly generate corresponding low-carbon alcohols from low-carbon olefins.
[0003] Existing conventional solid acid catalyst can be acidic zeolite, MoO3 / WO3, ion exchange resin (such as DOWEXR50, AMBERLYSTR 15 and D008 resin) and the solid acid catalyst (such as phosphoric acid loaded on silicon dioxide) of load.In order to promote olefin hydration reaction conversion rate to improve, patent application CN110665542A discloses a kind of isobutylene hydration reaction catalyst and its preparation method, catalyst adopts styrene, p-ethylstyrene, m-ethylstyrene, p-divinylbenzene and m-divinylbenzene as comonomer, and acts on suspension copolymerization with porogen, initiator and dispersant, obtains copolymer ball, and copolymer ball is obtained through extraction, drying, screening and sulfonation.This is the catalyst skeleton in-situ modification method, modification does not make full use of the huge inner surface of resin interior, acidic center adopts conventional sulfonic acid group simultaneously, acid strength is larger, and reaction conditions are not properly controlled when prone to more side reactions.
[0004] In view of the deficiencies in the activity and structure of existing hydration catalysts, the current development of new olefin hydration catalysts mainly focuses on optimizing catalyst formulations and preparation methods, improving catalytic hydration activity and the selectivity of catalyst structure to components, reducing the catalytic effect of catalyst activity centers on olefin self-polymerization, thereby reducing olefin polymerization, increasing the yield of low-carbon alcohols, and promoting the hydration equilibrium to move to the right. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the light olefin hydration catalyst in the prior art and the problem of low conversion rate in the light olefin hydration process, and to provide a light olefin hydration catalyst and a preparation method thereof, and a method for producing a light alcohol aqueous solution. The light olefin hydration catalyst can significantly improve the contact between water and olefin and the catalyst surface, and promote the improvement of the hydration conversion rate.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a low-carbon olefin hydration catalyst, wherein the hydration catalyst includes a resin white ball matrix, an adsorption layer and a reaction layer, the adsorption layer is grafted to the outer surface of the resin white ball matrix, and the reaction layer is grafted to the inner surface of the resin white ball matrix; the adsorption layer contains phenoxy, amide, pyrrol and furan groups; the reaction layer contains phenoxy, amide, sulfonic acid, phosphoric acid, pyrrol and furan groups.
[0007] A second aspect of the present invention provides a method for preparing a low-carbon olefin hydration catalyst, wherein the method comprises:
[0008] (1) in the presence of an adsorption component, subjecting the outer surface of a resin ball matrix to an adsorption treatment to obtain an adsorption-treated resin ball matrix;
[0009] (2) in the presence of reaction components, subjecting the inner surface of the resin ball matrix subjected to the adsorption treatment in step (1) to a reaction treatment to obtain a low-carbon olefin hydration catalyst;
[0010] The adsorption component contains phenoxy group, amide group, pyrrol group and furan group, and the reaction component contains phenoxy group, amide group, sulfonic acid group, phosphoric acid group, pyrrol group and furan group.
[0011] The third aspect of the present invention provides a method for producing a low-carbon alcohol aqueous solution, wherein the method comprises: in the presence of an olefin hydration catalyst, contacting a low-carbon olefin reaction raw material with water for a hydration reaction to obtain a low-carbon alcohol aqueous solution, wherein the hydration catalyst is the low-carbon olefin hydration catalyst described in the first aspect or the low-carbon olefin hydration catalyst obtained by the preparation method described in the second aspect.
[0012] The inventors of the present invention found in the process of low-carbon olefin hydration research that the olefin hydration is catalyzed by solid acid catalysts such as existing strong acid resins and ZSM-5 molecular sieves, and the olefin single-pass conversion rate is significantly low relative to the thermodynamic equilibrium conversion rate, which is mainly affected by factors of mass transfer and chemical equilibrium. Low-carbon olefins are generally insoluble in water, and even if the water-olefin ratio is greatly excessive, the two are still incompatible, and the effect is not obvious from the perspective of excessive reaction raw materials to further promote the hydration equilibrium to move to the right. Solid acid catalysts have good water binding properties, but poor compatibility with olefins. Olefins are difficult to adsorb on the solid acid catalytic surface after water saturation, thereby causing double bonds to be difficult to be activated. In order to improve the catalytic effect of solid acid, solid acid modification is mainly carried out around directions such as increasing acid strength and acid density, but this direction can cause side reactions such as olefins to overlap, resulting in a reduction in low-carbon alcohol yield and selectivity.
[0013] The low-carbon olefin hydration catalyst provided by the present invention solves the problems of poor contact between water and olefin on the catalytic surface and low yield and selectivity of low-carbon alcohol in the prior art from the perspective of microscopic mechanism. The hydration catalyst of the present invention is preferably further modified with a resin white ball with a low cross-linking degree as a matrix, and a low cross-linking degree can achieve a better swelling effect, which provides the possibility for good diffusion of reaction raw materials and reaction products.
[0014] The hydration catalyst provided by the present invention has an adsorption layer grafted on the outer surface of the resin ball matrix, and a reaction layer grafted on the inner surface of the resin ball matrix. The adsorption layer is grafted with a relatively high concentration of enophilic groups and a certain concentration of hydrophilic groups and low-carbon alcohol repelling groups. The relatively high concentration of enophilic groups enables the outer surface of the resin ball matrix to achieve enrichment of low-concentration olefins in the water emulsion, and diffuses them along the pores to the inside of the catalyst. The reaction layer is grafted on the huge inner surface of the resin, which is the main site of the hydration reaction of the olefin. The layer is grafted with a high concentration of hydrophilic groups (used to enrich water, and the water is diffused from the liquid phase body to the inner surface of the catalyst through the outer surface of the catalyst through the matching of different concentrations of hydrophilic groups on the outer surface and the inner surface), catalytic groups (used to activate olefins, and the acid strength is reasonably regulated through the coordinated matching of groups), low-carbon alcohol repelling groups (through the matching of different concentrations of repelling groups on the inner surface and the outer surface, the low-carbon alcohol generated by the reaction is transferred to the liquid phase body through the outer surface, and the hydration reaction is promoted to move to the right), and enophilic groups (used to enrich olefins and receive the olefins enriched on the outer surface). The water in the main body of the mixed liquid phase is continuously enriched from the main body of the liquid phase to the reaction layer based on the gradient change of the hydrophilic strength in the adsorption layer and the reaction layer, providing excess water for the hydration reaction microenvironment. The reaction layer is grafted with a high concentration of catalytic groups. After the enophilic groups continuously capture olefin molecules from the mixed liquid phase through the outer surface to the inner surface, under the activation of the catalytic groups with appropriate acid strength, the olefins react with the water molecules enriched on the inner surface. The low-carbon alcohols produced by hydration are continuously diffused from the inner surface to the main body of the liquid phase through the outer surface under the promotion of the low-carbon alcohol repelling groups, thereby moving the hydration equilibrium to the right. The presence of hydrophilic groups in the adsorption layer and the reaction layer achieves a large excess of microscopic water, thereby reducing the water-olefin ratio. The reduction of the water-olefin ratio also promotes the enrichment of olefin molecules on the enophilic groups, further promoting the movement of the hydration equilibrium. The appropriate acid strength of the inner surface of the catalyst suppresses the side reaction of olefin superposition, the resin pores are not easily blocked and deactivated, and the catalyst activity and stability are good. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] In the present invention, each group and its content in the adsorption layer and the reaction layer are measured by infrared spectroscopy. The specific test conditions are KBr tablets at 400cm -1 -4000cm -1 The content of each group in the adsorption layer and the reaction layer is measured step by step during the preparation process, that is, after the adsorption treatment is completed, the content of each group in the adsorption layer is measured after washing and drying; then after the reaction treatment is completed, the content of each group in the adsorption layer is measured after washing and drying. In the present invention, there is no special limitation on the test conditions. For example, 0.1g of dried resin white balls grafted with the adsorption layer can be randomly taken to measure the content of each group in the adsorption layer.
[0017] In the present invention, the resin ball matrix is a sphere or a nearly spherical structure containing pores inside.
[0018] The first aspect of the present invention provides a low-carbon olefin hydration catalyst, wherein the hydration catalyst includes a resin ball matrix, an adsorption layer and a reaction layer, the adsorption layer is grafted to the outer surface of the resin ball matrix, and the reaction layer is grafted to the inner surface of the resin ball matrix; the adsorption layer contains phenoxy, amide, pyrrol and furan groups; the reaction layer contains phenoxy, amide, sulfonic acid, phosphoric acid, pyrrol and furan groups.
[0019] In the present invention, there is no particular limitation on the specific type of the resin ball matrix, and any resin ball matrix conventionally defined in the art is applicable to the present invention. Preferably, the resin ball matrix is styrene-divinylbenzene resin.
[0020] In the present invention, preferably, the crosslinking degree of the styrene-divinylbenzene resin is 3-6%.
[0021] In the present invention, preferably, based on the dry resin ball matrix, the content of dangling double bonds in the resin ball matrix is 10-20 mmol / g.
[0022] In the present invention, preferably, the average pore size of the resin ball matrix is 15-40 nm.
[0023] In the present invention, there is no particular limitation on the source of the resin ball matrix, which can be obtained commercially or prepared according to the preparation method conventionally defined in the art. The present invention does not particularly limit its preparation method. For example, general resin balls prepared by suspension polymerization can be purchased, and they can be adapted to the present invention as long as the above parameters are met.
[0024] In the present invention, preferably, based on the total amount of the dry resin ball matrix and the adsorption layer, the content of phenoxy in the adsorption layer is 1.6-3.2 mmol / g, the content of amide is 0.6-1.2 mmol / g, the content of pyrrole is 0.85-1.7 mmol / g, and the content of furan is 0.15-0.3 mmol / g. By grafting the adsorption layer on the outer surface of the resin ball matrix and controlling the content of each group in the adsorption layer, olefins in the water-olefin emulsion can be enriched and low-carbon alcohols can be promoted to move into the liquid phase.
[0025] In the present invention, preferably, based on the total amount of the dry resin ball matrix, the adsorption layer and the reaction layer, in the reaction layer, the content of phenoxy is 0.6-1.2 mmol / g, the content of amide is 1-2 mmol / g, the content of sulfonic acid is 1.4-2.8 mmol / g, the content of phosphoric acid is 0.55-1.1 mmol / g, the content of pyrrole is 1.25-2.5 mmol / g, and the content of furan is 0.2-0.4 mmol / g. By grafting the reaction layer on the inner surface of the resin ball matrix and controlling the content of each group in the reaction layer, the water-olefin two-phase contact and reaction can be promoted, and the low-carbon alcohol produced by the reaction can be transferred to the outer surface by mass transfer.
[0026] A second aspect of the present invention provides a method for preparing a low-carbon olefin hydration catalyst, wherein the method comprises:
[0027] (1) in the presence of an adsorption component, subjecting the outer surface of a resin ball matrix to an adsorption treatment to obtain an adsorption-treated resin ball matrix;
[0028] (2) in the presence of reaction components, subjecting the inner surface of the resin ball matrix subjected to the adsorption treatment in step (1) to a reaction treatment to obtain a low-carbon olefin hydration catalyst;
[0029] The adsorption component contains phenoxy group, amide group, pyrrol group and furan group, and the reaction component contains phenoxy group, amide group, sulfonic acid group, phosphoric acid group, pyrrol group and furan group.
[0030] In the present invention, in step (1), the type, material, characteristic parameters and source of the resin ball matrix have been described in the first aspect and will not be repeated here.
[0031] In the present invention, preferably, in step (1), the adsorption treatment causes the outer surface of the resin ball matrix to be grafted with an adsorption layer, and the adsorption layer contains phenoxy, amide, pyrrol and furan groups.
[0032] In the present invention, the content of each group in the adsorption layer has been described in the first aspect and will not be repeated here.
[0033] In the present invention, preferably, in step (1), the adsorption component is provided by a solution containing the adsorption component, and the solution containing the adsorption component contains the adsorption component, a first initiator, a first solvent and a polyether.
[0034] In the present invention, preferably, in step (1), in the solution containing the adsorption component, the mass ratio of the adsorption component: the first initiator: the first solvent: the polyether is (2.5-4.8): (0.1-0.2): (90-94): (3.2-4.6).
[0035] In the present invention, preferably, the average molecular weight of the polyether is 600-1500.
[0036] In the present invention, the first solvent has a wide range of types, and those skilled in the art can select it according to actual needs. Preferably, in step (1), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene.
[0037] In the present invention, the first initiator has a wide range of types, and those skilled in the art can select it according to actual needs. Preferably, in step (1), the first initiator is selected from at least one of azo, organic peroxide, inorganic peroxide and redox initiators, more preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate and hydrogen peroxide, and more preferably benzoyl peroxide.
[0038] In the present invention, preferably, in step (1), the adsorption component is provided by phenoxy derivatives, amide derivatives, pyrrole derivatives and furan derivatives.
[0039] In the present invention, preferably, in the adsorption component, the molar ratio of phenoxy derivatives: amide derivatives: pyrrole derivatives: furan derivatives is (1.9-3.9): (0.7-1.5): (1.0-2.1): (0.16-0.37).
[0040] In the present invention, there is no particular limitation on the specific types of phenoxy derivatives. Preferably, the phenoxy group is provided by a phenoxy derivative, preferably provided by at least one of 4-methoxystyrene, allylphenyl ether and phenylvinyl ether.
[0041] In the present invention, there is no particular limitation on the specific types of amide derivatives. Preferably, the amide group is provided by an amide derivative, preferably provided by at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide.
[0042] In the present invention, there is no particular limitation on the specific types of pyrrole derivatives. Preferably, the pyrrole group is provided by a pyrrole derivative, preferably provided by at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one.
[0043] In the present invention, there is no particular limitation on the specific types of furan derivatives. Preferably, the furanyl group is provided by a furan derivative, preferably 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan.
[0044] In the present invention, there is no particular limitation on the method and conditions of the adsorption treatment. Preferably, in step (1), the adsorption treatment comprises: immersing the solution containing the adsorption component in contact with the resin ball matrix, the liquid-to-solid volume ratio is 1-3, the treatment temperature is 60-80°C, and the treatment time is 1.5-3h. In the present invention, the outer surface of the resin ball matrix is treated with a solution containing the adsorption component, and during the adsorption treatment, the outer edge of the pores of the resin ball matrix close to the outer surface is blocked with the help of polyether (polyether exists in the form of gel solution). The adsorption treatment only treats the outer surface of the resin ball matrix, so that the dangling double bonds on the outer surface of the resin ball matrix are completely reacted, and then the outer surface will not be grafted with reactive groups again during the subsequent reaction treatment, thereby avoiding the reaction treatment from affecting the outer surface of the resin ball matrix.
[0045] In the present invention, preferably, step (1) further comprises subjecting the adsorption product after the adsorption treatment to adsorption post-treatment in a post-treatment agent A. The specific operation mode of the adsorption post-treatment is not particularly limited in the present invention. Preferably, the adsorption product after the adsorption treatment is subjected to equal volume replacement in the post-treatment agent A.
[0046] In the present invention, there is no particular limitation on the type of post-treatment agent A. Preferably, the post-treatment agent A is benzene and / or acetonitrile, more preferably acetonitrile.
[0047] In the present invention, the range of selection of conditions for post-adsorption treatment is relatively wide, and the polyether residue attached to the outer surface of the adsorption treatment substrate can be removed by post-adsorption treatment, so as to prepare for subsequent further modification. Preferably, the conditions for post-adsorption treatment include: a soaking temperature of 50-70°C, a soaking time of 0.5-1h, and a soaking number of 1-3 times. In the present invention, the soaking number is the aforementioned equal volume replacement number.
[0048] In the present invention, preferably, in step (2), the reaction treatment allows the inner surface of the resin white ball matrix after the adsorption treatment in step (1) to be grafted with a reaction layer, and the reaction layer contains phenoxy, amide, sulfonic acid, phosphoric acid, pyrrol and furan groups.
[0049] In the present invention, the content of each group in the reaction layer has been described in the first aspect and will not be repeated here.
[0050] In the present invention, preferably, in step (2), the reaction components are provided by a solution containing the reaction components, and the solution containing the reaction components contains the reaction components, the second initiator and the second solvent.
[0051] In the present invention, there is no particular limitation on the content of each component in the solution containing the reaction components. Preferably, in step (2), in the solution containing the reaction components, the mass ratio of the reaction components: the second initiator: the second solvent is (2.7-4.9): (0.1-0.2): (90-94).
[0052] In the present invention, preferably, the reaction components are selected from phenoxy derivatives, amide derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives and furan derivatives.
[0053] In the present invention, there is no particular limitation on the amount of each derivative in the reaction component, and the purpose is to meet the content of the required group. Preferably, in step (2), in the reaction component, the molar ratio of phenoxy derivatives: amide derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is (0.7-1.5): (1.1-2.5): (1.6-3.4): (0.7-1.4): (1.5-2.9): (0.23-0.49).
[0054] In the present invention, the specific types of phenoxy derivatives, amide derivatives, pyrrole derivatives and furan derivatives selected in step (2) may be the same as or different from the types of the derivatives in the aforementioned step (1), but are preferably the same.
[0055] In the present invention, preferably, the phosphate group is provided by a phosphate derivative, and more preferably by at least one of (2-fluoro-3,7-dimethyloct-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate.
[0056] In the present invention, preferably, the sulfonic acid group is provided by a sulfonic acid derivative, and more preferably by at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate.
[0057] In the present invention, the type of the second solvent is not particularly limited, and the second solvent may be the same as or different from the first solvent.
[0058] In the present invention, the type of the second initiator is not particularly limited, and the second initiator may be the same as or different from the first initiator.
[0059] In the present invention, there is no particular limitation on the method and conditions of the reaction treatment. Preferably, in step (2), the reaction treatment comprises: immersing the solution containing the reaction components in contact with the resin white ball matrix after the adsorption treatment described in step (1), with a liquid-to-solid volume ratio of 1-3, a treatment temperature of 60-80°C, and a treatment time of 1.5-3h.
[0060] In the present invention, preferably, step (2) further comprises subjecting the reaction product to post-reaction treatment in post-treatment agent B. Preferably, the reaction product after the reaction treatment is subjected to equal volume replacement in post-treatment agent B.
[0061] In the present invention, the selection range of the post-treatment agent B is relatively wide. Preferably, the post-treatment agent B is selected from at least one of anhydrous ethanol, anhydrous acetone and anhydrous methanol, and more preferably anhydrous ethanol.
[0062] In the present invention, the range of post-reaction treatment conditions is relatively wide, and the residual monomers in the pores are removed and the pore structure is improved by post-reaction treatment. Preferably, the post-reaction treatment conditions include: a soaking temperature of 60-80°C, a soaking time of 1-2h, and a soaking number of 1-3 times. In the present invention, the soaking number is the aforementioned equal volume replacement number.
[0063] In the present invention, preferably, the post-reaction treatment further comprises drying the post-reaction treatment product.
[0064] In the present invention, the drying treatment conditions can be selected in a wide range. Preferably, the drying treatment conditions include: a drying temperature of 100-120°C and a drying time of 0.5-1h. In the present invention, preferably, the drying treatment is performed under a nitrogen atmosphere.
[0065] The third aspect of the present invention provides a method for producing an aqueous solution of low-carbon alcohols, wherein the method comprises: in the presence of a hydration catalyst, contacting a low-carbon olefin reaction raw material with water for a hydration reaction to obtain an aqueous solution of low-carbon alcohols, wherein the hydration catalyst is the low-carbon olefin hydration catalyst described in the first aspect or the low-carbon olefin hydration catalyst obtained by the preparation method described in the second aspect.
[0066] In the present invention, preferably, based on the total amount of the olefin reaction raw material, the content of the light olefin in the olefin reaction raw material is 10-100 volume %.
[0067] In the present invention, preferably, the low-carbon olefin is C3 and / or C4 olefin.
[0068] In the present invention, preferably, the light olefin hydration reaction is carried out in a fixed bed reactor.
[0069] In the present invention, the conditions for the hydration reaction can be selected in a wide range. Preferably, the conditions for the hydration reaction include: a temperature of 120-160°C, a pressure of 2000-4000 kPa in terms of gauge pressure, and a volume space velocity of 0.5-3 h / min for the olefin reaction raw material. -1 , the molar ratio of water to olefin reaction raw material is 6-15.
[0070] In the present invention, preferably, the single-pass olefin conversion rate is greater than 32%, and the low-carbon alcohol selectivity is greater than 92%.
[0071] The present invention will be described in detail below through examples.
[0072] In the present invention, the content of each group in the reaction layer and the adsorption layer is measured by the test method described above.
[0073] In the present invention, component analysis adopts 20A high performance liquid chromatography system (Shimadzu Corporation, Japan, equipped with autosampler, 10AT and 10AD pumps, 20A multi-wavelength ultraviolet detector); ACQUITY UPLC / Xevo G2QTOF ultra-high performance liquid chromatography high-resolution tandem mass spectrometry (Waters Corporation, USA, equipped with autosampler, diode array ultraviolet detector). High performance liquid chromatography conditions: chromatographic column: Zorbax Eclipse Plus C18 (4.6mm×150mm, 5μm), mobile phase: water (containing 0.06%v phosphoric acid): acetonitrile = 95:5, flow rate: 1.0mL / min, detection wavelength: 210nm, column temperature: 35°C, injection volume: 1μL. Ultra-high performance liquid chromatography conditions: chromatographic column: HSST3 (2.1mm×100mm, 1.7μm); mobile phase: water, methanol; gradient elution (positive ion mode): 0minV(water):V(methanol)=85:15, 2.5min laterV(water):v(methanol)=55:35, 4min laterV(water):V(methanol):10:90, flow rate: 0.45mL / min; gradient elution (negative ion mode): 0minV(water):V(methanol):70:30, 2.5min laterV(water):V(methanol)=55:35, 3.5min laterV(water):V(methanol)=10:90; flow rate: 0.45mL / min; column temperature: 30℃; injection volume: 3μL. Mass spectrometry conditions: electrospray ionization source (ESI), positive or negative ion scanning mode, capillary voltage 2 kV, cone voltage 30 eV, ion source temperature: 120 ° C, desolvation temperature 450 ° C, cone gas flow rate 50 L / h, desolvation gas (N2) flow rate 900 L / h.
[0074] Example 1
[0075] The composition of the olefin reaction raw materials in this embodiment, by volume percentage, includes: 33.0% isobutane, 8.7% butane, 56.3% n-butene, and 2.0% pentane.
[0076] In this embodiment, the resin ball matrix is a general resin ball made by purchased suspension polymerization, and the product indicators are that the resin ball matrix is styrene-divinylbenzene resin; the crosslinking degree of styrene-divinylbenzene resin is 4.5%, the content of pendant double bonds in the dry-based resin ball is 15.1 mmol / g, and the average pore size is 27.6 nm.
[0077] In step (1), the solution containing the adsorption component is contacted with the resin ball matrix, so that the outer surface of the resin ball matrix is grafted with the adsorption layer. In the solution containing the adsorption component, the mass ratio of the adsorption component: the first initiator: the first solvent: the polyether (average molecular weight is 1000) is 3.6:0.1:92:3.9. The first solvent is toluene. The first initiator is benzoyl peroxide. The adsorption component contains phenoxy derivatives, amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: pyrrole derivatives: furan derivatives is 2.9:1.1:1.6:0.26. Phenoxy derivatives are provided by allyl phenyl ether. Amide derivatives are provided by N,N-methylenebisacrylamide. Pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. Furan derivatives are provided by 2-(1-propylene-2-yl) furan. The adsorption treatment conditions include: the solution containing the adsorption component is immersed in contact with the resin ball matrix of step (1), the liquid-to-solid volume ratio is 2, the treatment temperature is 70° C., and the treatment time is 2.25 hours. Based on the total amount of the dry resin ball matrix and the adsorption layer, the content of the phenoxy group in the adsorption layer is 2.3 mmol / g, the content of the amide group is 0.9 mmol / g, the content of the pyrrolyl group is 1.3 mmol / g, and the content of the furanyl group is 0.21 mmol / g.
[0078] Step (1) further comprises subjecting the resin ball matrix treated with the adsorption component to adsorption post-treatment in post-treatment agent A. Post-treatment agent A is acetonitrile. Conditions for adsorption post-treatment include: soaking at 60° C. for 0.7 h, and equal volume replacement twice.
[0079] In step (2), the solution containing the reaction component is contacted with the resin ball matrix after the adsorption treatment, so that the inner surface of the resin ball matrix after the adsorption component treatment is grafted with the reaction layer. In the solution containing the reaction component, the mass ratio of the reaction component: the second initiator: the second solvent is 3.8:0.1:92. The second solvent is toluene. The second initiator is benzoyl peroxide. The reaction component contains phenoxy derivatives, amide derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 1.1:1.3:2.5:0.9:2.2:0.36. The phenoxy derivative is provided by allyl phenyl ether. The amide derivative is provided by N,N-methylenebisacrylamide. The phosphoric acid derivative is provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivatives are provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivatives are provided by 2-(1-propylene-2-yl)furan. The reaction treatment conditions include: the solution containing the reaction components is immersed in contact with the resin white ball matrix after the adsorption treatment described in step (1), the liquid-to-solid volume ratio is 2, the treatment temperature is 70°C, and the treatment time is 2.3h. Based on the total amount of the dry resin white ball matrix, the adsorption layer and the reaction layer, the content of phenoxy in the reaction layer is 0.9mmol / g, the content of amide group is 1.1mmol / g, the content of sulfonic acid group is 2.0mmol / g, the content of phosphate group is 0.74mmol / g, the content of pyrrole group is 1.8mmol / g, and the content of furan group is 0.3mmol / g.
[0080] Step (2) further comprises subjecting the reaction product to post-reaction treatment in a post-treatment agent B. The post-treatment agent B is anhydrous ethanol. The conditions for the post-reaction treatment include: a soaking temperature of 70° C., a soaking time of 1.5 h, soaking and replacing with equal volumes twice, a drying temperature of 110° C., and a drying time of 0.7 h.
[0081] The prepared low-carbon olefin hydration catalyst is used in the hydration of low-carbon olefins. The low-carbon olefin hydration catalyst is filled in a fixed bed reactor, and a mixture of olefins and desalted water is contacted with the low-carbon olefin hydration catalyst to carry out an olefin hydration reaction to obtain an aqueous solution containing low-carbon alcohols. The conditions for the olefin hydration reaction include: a temperature of 140°C, a pressure of 3000 kPa on a gauge pressure, and a volume space velocity of 1.7 h / min for the olefin reaction raw material. -1 , the molar ratio of water to olefin reaction raw material is 10.
[0082] The single-pass olefin conversion rate of olefin hydration is 37.5%, and the selectivity for low-carbon alcohols is 95.3%.
[0083] Example 2
[0084] The olefin reaction raw material of Example 1 was selected.
[0085] In this embodiment, the resin ball matrix is a general resin ball purchased from suspension polymerization, and the resin ball matrix is styrene-divinylbenzene resin; the crosslinking degree of styrene-divinylbenzene resin is 3.2%, the content of dangling double bonds in the dry-based resin ball is 18.7 mmol / g, and the average pore size is 38.4 nm.
[0086] In step (1), the solution containing the adsorption component is contacted with the resin ball matrix, so that the outer surface of the resin ball matrix is grafted with the adsorption layer. In the solution containing the adsorption component, the mass ratio of the adsorption component: the first initiator: the first solvent: the polyether (average molecular weight of 700) is 4.7:0.2:91:3.3. The first solvent is toluene. The first initiator is benzoyl peroxide. The adsorption component contains phenoxy derivatives, amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: pyrrole derivatives: furan derivatives is 3.8:1.4:2.0:0.36. The phenoxy derivative is provided by allyl phenyl ether. The amide derivative is provided by N,N-methylenebisacrylamide. The pyrrole derivative is provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivative is provided by 2-(1-propylene-2-yl) furan. The adsorption treatment conditions include: the solution containing the adsorption component is immersed in contact with the resin ball matrix of step (1), the liquid-to-solid volume ratio is 3, the treatment temperature is 78° C., and the treatment time is 2.7 hours. Based on the total amount of the dry resin ball matrix and the adsorption layer, the content of the phenoxy group in the adsorption layer is 3.1 mmol / g, the content of the amide group is 1.1 mmol / g, the content of the pyrrolyl group is 1.6 mmol / g, and the content of the furanyl group is 0.29 mmol / g.
[0087] Step (1) further comprises subjecting the resin ball matrix after adsorption treatment to adsorption post-treatment in post-treatment agent A. Post-treatment agent A is acetonitrile. Conditions for adsorption post-treatment include: soaking treatment at 68° C. for 0.9 h, and equal volume replacement for 3 times.
[0088] In step (2), the solution containing the reaction components is contacted with the resin ball matrix after the adsorption treatment, so that the inner surface of the resin ball matrix after the adsorption treatment is grafted with the reaction layer. In the solution containing the reaction components, the mass ratio of the reaction components: the second initiator: the second solvent is 4.8:0.2:91. The second solvent is toluene. The second initiator is benzoyl peroxide. The reaction components contain phenoxy derivatives, amide derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 1.4:2.4:3.3:1.3:2.8:0.47. The phenoxy derivatives are provided by allyl phenyl ether. The amide derivatives are provided by N,N-methylenebisacrylamide. The phosphoric acid derivatives are provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivatives are provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivatives are provided by 2-(1-propylene-2-yl)furan. The reaction treatment conditions include: the solution containing the reaction components is immersed in contact with the resin white ball matrix after the adsorption treatment in step (1), the liquid-to-solid volume ratio is 3, the treatment temperature is 78°C, and the treatment time is 2.6h. Based on the total amount of the dry resin white ball matrix, the adsorption layer and the reaction layer, the content of the phenoxy group in the reaction layer is 1.1mmol / g, the content of the amide group is 1.9mmol / g, the content of the sulfonic acid group is 2.6mmol / g, the content of the phosphate group is 1.02mmol / g, the content of the pyrrole group is 2.2mmol / g, and the content of the furan group is 0.37mmol / g.
[0089] Step (2) further comprises subjecting the reaction product to post-reaction treatment in a post-treatment agent B. The post-treatment agent B is anhydrous ethanol. The conditions for the post-reaction treatment include: a soaking temperature of 78° C., a soaking time of 1.7 h, soaking and replacing with equal volume 3 times, a drying temperature of 117° C., and a drying time of 0.9 h.
[0090] The reaction method of Example 1 is the same as that of Example 1, except that the conditions for the olefin hydration reaction include: a temperature of 130° C., a pressure of 2500 kPa on a gauge pressure basis, and a volumetric space velocity of 0.6 h / min of the olefin reaction raw material. -1 , the molar ratio of water to olefin reaction raw material is 14.
[0091] The single-pass olefin conversion rate of olefin hydration is 40.2%, and the selectivity for low-carbon alcohols is 97.4%.
[0092] Example 3
[0093] The olefin reaction raw material of Example 1 was selected.
[0094] In this embodiment, the resin ball matrix is a general resin ball purchased from suspension polymerization, and the resin ball matrix is styrene-divinylbenzene resin; the crosslinking degree of styrene-divinylbenzene resin is 5.8%, the content of dangling double bonds in the dry-based resin ball is 10.7 mmol / g, and the average pore size is 16.4 nm.
[0095] In step (1), the solution containing the adsorption component is contacted with the resin ball matrix, so that the outer surface of the resin ball matrix is grafted with the adsorption layer. In the solution containing the adsorption component, the mass ratio of the adsorption component: the first initiator: the first solvent: the polyether (average molecular weight is 1400) is 2.6:0.2:93:4.5. The first solvent is toluene. The first initiator is benzoyl peroxide. The adsorption component contains phenoxy derivatives, amide derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: pyrrole derivatives: furan derivatives is 2.0:0.8:1.2:0.18. The phenoxy derivative is provided by allyl phenyl ether. The amide derivative is provided by N,N-methylenebisacrylamide. The pyrrole derivative is provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivative is provided by 2-(1-propylene-2-yl) furan. The adsorption treatment conditions include: the solution containing the adsorption component is immersed in contact with the resin ball matrix of step (1), the liquid-to-solid volume ratio is 1, the treatment temperature is 62° C., and the treatment time is 1.7 h. Based on the total amount of the dry resin ball matrix and the adsorption layer, the content of the phenoxy group in the adsorption layer is 1.7 mmol / g, the content of the amide group is 0.68 mmol / g, the content of the pyrrolyl group is 1.02 mmol / g, and the content of the furanyl group is 0.15 mmol / g.
[0096] Step (1) further comprises subjecting the resin ball matrix after adsorption treatment to adsorption post-treatment in post-treatment agent A. Post-treatment agent A is acetonitrile. Conditions for adsorption post-treatment include: soaking treatment at 52° C. for 0.6 h, and equal volume replacement for 3 times.
[0097] In step (2), the solution containing the reaction components is contacted with the resin ball matrix after the adsorption treatment, so that the inner surface of the resin ball matrix after the adsorption treatment is grafted with the reaction layer. In the solution containing the reaction components, the mass ratio of the reaction components: the second initiator: the second solvent is 2.8:0.2:93. The second solvent is toluene. The second initiator is benzoyl peroxide. The reaction components contain phenoxy derivatives, amide derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives, and furan derivatives, wherein the molar ratio of phenoxy derivatives: amide derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is 0.8:1.2:1.7:0.8:1.6:0.25. The phenoxy derivatives are provided by allyl phenyl ether. The amide derivatives are provided by N,N-methylenebisacrylamide. The phosphoric acid derivatives are provided by [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonohydrogen phosphate. The sulfonic acid derivatives are provided by (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)). The pyrrole derivatives are provided by 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole. The furan derivatives are provided by 2-(1-propylene-2-yl)furan. The reaction treatment conditions include: the solution containing the reaction components is immersed in contact with the resin white ball matrix after the adsorption treatment in step (1), the liquid-to-solid volume ratio is 1, the treatment temperature is 62°C, and the treatment time is 1.7h. Based on the total amount of the dry resin white ball matrix, the adsorption layer and the reaction layer, the content of the phenoxy group in the reaction layer is 0.7mmol / g, the content of the amide group is 1.05mmol / g, the content of the sulfonic acid group is 1.49mmol / g, the content of the phosphate group is 0.7mmol / g, the content of the pyrrole group is 1.4mmol / g, and the content of the furan group is 0.22mmol / g.
[0098] Step (2) further comprises subjecting the reaction product to post-reaction treatment in a post-treatment agent B. The post-treatment agent B is anhydrous ethanol. The conditions for the post-reaction treatment include: a soaking temperature of 63° C., a soaking time of 1.4 h, equal volume soaking and replacement once, a drying temperature of 103° C., and a drying time of 0.6 h.
[0099] The reaction method of Example 1 is the same as that of Example 1, except that the conditions for the olefin hydration reaction include: a temperature of 150° C., a pressure of 3600 kPa on a gauge pressure basis, and a volumetric space velocity of 2.5 h / min of the olefin reaction raw material. -1 , the molar ratio of water to olefin reaction raw material is 8.
[0100] The single-pass olefin conversion rate of olefin hydration is 33.7%, and the selectivity for low-carbon alcohols is 93.5%.
[0101] Example 4
[0102] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 15.9% isobutane, 7.1% normal butane, 75.7% normal butene, and 1.3% pentane.
[0103] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 43.6%, and the selectivity of low-carbon alcohols was 97.5%.
[0104] Example 5
[0105] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 6.3% isobutane, 2.4% normal butane, 90.9% normal butene, and 0.4% pentane.
[0106] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 45.8%, and the selectivity of low-carbon alcohols was 97.6%.
[0107] Example 6
[0108] The method of Example 2 is followed, except that the composition of the olefin reaction raw materials in this example, by volume percentage, includes: 52.1% isobutane, 13.2% normal butane, 29.4% normal butene, and 5.3% pentane.
[0109] According to the reaction method and conditions of Example 2, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 38.2%, and the selectivity of low-carbon alcohols was 97.1%.
[0110] Comparative Example 1
[0111] The olefin reaction raw material used in Example 5 was selected.
[0112] According to the reaction method of Example 5, the olefin hydration reactor was filled with Suqing brand macroporous strong acid resin D002GH, the reaction temperature was 170°C, the reaction pressure was 85 kg, and the reaction mass space velocity was 1h -1 The single-pass conversion rate of n-butene is 12.3%, and the selectivity of low-carbon alcohols is 95.2%.
[0113] Comparative Example 2
[0114] The method of Example 3 is different in that the present comparative example does not carry out the adsorption treatment in step (1), and directly uses the reaction components to carry out the reaction treatment in step (2) on the resin ball matrix.
[0115] According to the reaction materials, reaction method and conditions of Example 3, in the olefin hydration reactor, the single-pass olefin conversion rate of olefin hydration was 20.4%, and the selectivity of low-carbon alcohols was 96.2%.
[0116] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for hydration of light olefins, characterized in that: The hydration catalyst comprises a resin ball matrix, an adsorption layer and a reaction layer, wherein the adsorption layer is grafted onto the outer surface of the resin ball matrix, and the reaction layer is grafted onto the inner surface of the resin ball matrix; the adsorption layer contains phenoxy, amide, pyrrol and furan groups; the reaction layer contains phenoxy, amide, sulfonic acid, phosphoric acid, pyrrol and furan groups.
2. The light olefin hydration catalyst according to claim 1, wherein The resin white ball matrix is styrene-divinylbenzene resin; Preferably, the crosslinking degree of the styrene-divinylbenzene resin is 3-6%; Preferably, based on the dry resin ball matrix, the content of pendant double bonds in the resin ball matrix is 10-20 mmol / g; Preferably, the average pore size of the resin ball matrix is 15-40 nm.
3. The low-carbon olefin hydration catalyst according to claim 1 or 2, wherein Based on the total amount of the dry resin white ball matrix and the adsorption layer, in the adsorption layer, the content of phenoxy is 1.6-3.2 mmol / g, the content of amide is 0.6-1.2 mmol / g, the content of pyrrol is 0.85-1.7 mmol / g, and the content of furan is 0.15-0.3 mmol / g.
4. The light olefin hydration catalyst according to claim 3, wherein Based on the total amount of the dry resin white ball matrix, the adsorption layer and the reaction layer, in the reaction layer, the content of phenoxy is 0.6-1.2 mmol / g, the content of amide is 1-2 mmol / g, the content of sulfonic acid is 1.4-2.8 mmol / g, the content of phosphoric acid is 0.55-1.1 mmol / g, the content of pyrrolyl is 1.25-2.5 mmol / g, and the content of furanyl is 0.2-0.4 mmol / g.
5. A method for preparing a low-carbon olefin hydration catalyst, wherein: The method includes: (1) in the presence of an adsorption component, subjecting the outer surface of a resin ball matrix to an adsorption treatment to obtain an adsorption-treated resin ball matrix; (2) in the presence of reaction components, subjecting the inner surface of the resin ball matrix subjected to the adsorption treatment in step (1) to a reaction treatment to obtain a low-carbon olefin hydration catalyst; The adsorption component contains phenoxy group, amide group, pyrrol group and furan group, and the reaction component contains phenoxy group, amide group, sulfonic acid group, phosphoric acid group, pyrrol group and furan group.
6. The method according to claim 5, wherein: In step (1), the resin ball matrix is styrene-divinylbenzene resin; Preferably, the crosslinking degree of the styrene-divinylbenzene resin is 3-6%; Preferably, based on the dry resin ball matrix, the content of pendant double bonds in the resin ball matrix is 10-20 mmol / g; Preferably, the average pore size of the resin ball matrix is 15-40 nm.
7. The method according to claim 5 or 6, wherein: In step (1), the adsorption treatment causes the outer surface of the resin ball matrix to be grafted with an adsorption layer, wherein the adsorption layer contains phenoxy, amide, pyrrol and furan groups; Preferably, based on the total amount of the dry resin white ball matrix and the adsorption layer, in the adsorption layer, the content of phenoxy is 1.6-3.2 mmol / g, the content of amide is 0.6-1.2 mmol / g, the content of pyrrol is 0.85-1.7 mmol / g, and the content of furan is 0.15-0.3 mmol / g.
8. The method according to any one of claims 5 to 7, wherein: In step (1), the adsorption component is provided by a solution containing the adsorption component, and the solution containing the adsorption component contains the adsorption component, a first initiator, a first solvent and a polyether; And / or, in step (1), in the solution containing the adsorption component, the mass ratio of the adsorption component: the first initiator: the first solvent: the polyether is (2.5-4.8): (0.1-0.2): (90-94): (3.2-4.6); And / or, the average molecular weight of the polyether is 600-1500; And / or, in step (1), the first solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, in step (1), the first initiator is selected from at least one of azo, organic peroxide, inorganic peroxide and redox initiators, preferably at least one of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate and hydrogen peroxide, more preferably benzoyl peroxide; And / or, in step (1), the adsorption component is provided by phenoxy derivatives, amide derivatives, pyrrole derivatives and furan derivatives; And / or, in step (1), in the adsorption component, the molar ratio of phenoxy derivatives: amide derivatives: pyrrole derivatives: furan derivatives is (1.9-3.9): (0.7-1.5): (1.0-2.1): (0.16-0.37); And / or, the phenoxy group is provided by a phenoxy derivative, preferably provided by at least one of 4-methoxystyrene, allylphenyl ether and phenyl vinyl ether; and / or, the amide group is provided by an amide derivative, preferably provided by at least one of N,N'-dihydroxyethylbisacrylamide, N,N-methylenebisacrylamide and hexamethylenebisacrylamide; and / or, the pyrrole group is provided by a pyrrole derivative, preferably provided by at least one of 3-isopropenyl-1-methyl-pyrrole, 1-(3-butene-1-yl)-2-vinyl-1H-pyrrole and 5-allyl-4-methoxy-1,5-dihydro-2H-pyrrol-2-one; and / or, the furanyl group is provided by a furan derivative, preferably 2-(1-propen-2-yl)furan and / or 2-(2-pentenyl)furan; And / or, in step (1), the adsorption treatment comprises: immersing the solution containing the adsorption component into contact with the resin ball matrix, with a liquid-to-solid volume ratio of 1-3, a treatment temperature of 60-80°C, and a treatment time of 1.5-3h.
9. The method according to claim 8, wherein: Step (1) further comprises subjecting the adsorption product after the adsorption treatment to adsorption post-treatment in a post-treatment agent A; And / or, the post-treatment agent A is benzene and / or acetonitrile, preferably acetonitrile; And / or, the post-adsorption treatment conditions include: a soaking temperature of 50-70° C., a soaking time of 0.5-1 h, and a soaking number of 1-3 times.
10. The method according to any one of claims 5 to 7, wherein: In step (2), the reaction treatment is performed so that the inner surface of the resin ball matrix after the adsorption treatment in step (1) is grafted with a reaction layer, and the reaction layer contains phenoxy, amide, sulfonic acid, phosphoric acid, pyrrol and furan groups; Preferably, based on the total amount of the dry resin white ball matrix, the adsorption layer and the reaction layer, in the reaction layer, the content of phenoxy is 0.6-1.2 mmol / g, the content of amide is 1-2 mmol / g, the content of sulfonic acid is 1.4-2.8 mmol / g, the content of phosphoric acid is 0.55-1.1 mmol / g, the content of pyrrolyl is 1.25-2.5 mmol / g, and the content of furanyl is 0.2-0.4 mmol / g.
11. The method according to any one of claims 5 to 7, wherein: In step (2), the reaction components are provided by a solution containing the reaction components, and the solution containing the reaction components contains the reaction components, a second initiator and a second solvent; And / or, in step (2), in the solution containing the reaction components, the mass ratio of the reaction components: the second initiator: the second solvent is (2.7-4.9): (0.1-0.2): (90-94); And / or, in step (2), the reaction components are selected from phenoxy derivatives, amide derivatives, sulfonic acid derivatives, phosphoric acid derivatives, pyrrole derivatives and furan derivatives; And / or, in step (2), in the reaction components, the molar ratio of phenoxy derivatives: amide derivatives: sulfonic acid derivatives: phosphoric acid derivatives: pyrrole derivatives: furan derivatives is (0.7-1.5): (1.1-2.5): (1.6-3.4): (0.7-1.4): (1.5-2.9): (0.23-0.49); and / or, the phosphate group is provided by a phosphate derivative, preferably by at least one of (2-fluoro-3,7-dimethylocta-1,6-dien-3-yl)phosphonyl hydrogen phosphate, [2-methyl-2-(4-methylpent-3-enyl)cyclopropyl]methylphosphonyl hydrogen phosphate and 2-(phosphoryloxy)propane-1,3-diyl dimethacrylate; and / or, the sulfonic acid group is provided by a sulfonic acid derivative, preferably by at least one of 4-hydroxy-6-(prop-2-enoylamino)naphthalene-2-sulfonic acid, (Z)-4',4"'-(ethylene-1,2-diyl)bis(([[1,1'-biphenyl]-4-sulfonic acid)) and 4-{(E)-2-[3,5-di(sulfooxy)phenyl]vinyl}phenyl hydrosulfate; And / or, in step (2), the reaction treatment comprises: immersing the solution containing the reaction components in contact with the resin white ball matrix after the adsorption treatment described in step (1), with a liquid-to-solid volume ratio of 1-3, a treatment temperature of 60-80°C, and a treatment time of 1.5-3h.
12. The method according to claim 11, wherein: Step (2) further comprises subjecting the reaction product to post-reaction treatment in a post-treatment agent B; And / or, the post-treatment agent B is selected from at least one of anhydrous ethanol, anhydrous acetone and anhydrous methanol, preferably anhydrous ethanol; And / or, the post-reaction treatment conditions include: soaking temperature of 60-80° C., soaking time of 1-2 h, soaking times of 1-3 times; Preferably, the post-reaction treatment further comprises drying the post-reaction treatment product; Preferably, the conditions for the drying treatment include: a drying temperature of 100-120° C. and a drying time of 0.5-1 h.
13. A method for producing a low-carbon alcohol aqueous solution, wherein: The method comprises: in the presence of a hydration catalyst, contacting a low-carbon olefin reaction raw material with water for a hydration reaction to obtain a low-carbon alcohol aqueous solution, wherein the hydration catalyst is the low-carbon olefin hydration catalyst described in any one of claims 1 to 4 or the low-carbon olefin hydration catalyst obtained by the preparation method described in any one of claims 5 to 12.
14. The method according to claim 13, wherein: The content of low-carbon olefins in the olefin reaction raw materials is 10-100 volume % based on the total amount of the olefin reaction raw materials; Preferably, the light olefin is C3 and / or C4 olefin; Preferably, the light olefin hydration reaction is carried out in a fixed bed reactor; And / or, the conditions of the hydration reaction include: temperature of 120-160°C, pressure of 2000-4000 kPa in gauge pressure, volume space velocity of olefin reaction raw material of 0.5-3h -1 , the molar ratio of water to olefin reaction raw material is 6-15.
Citation Information
Patent Citations
Catalyst for isobutylene hydration reaction and preparation method thereof
CN110665542A
Pyrrolyl modification complex function polymeric adsorbent and manufacture method thereof
CN101245155A
Modified hollow ceramic fiber and preparation and application thereof
CN115957812A
Graft-modified product, adhesive, olefin resin composition, and laminate
CN116438076A
Process for the continuous production of lower aliphatic alcohols
US4340769A
Cited By
Low-carbon olefin hydration product separation fiber membrane as well as preparation method and application thereof
CN119656876A
A low-carbon olefin hydration product separation fiber membrane and a preparation method and application thereof
CN119656876B